Cyclopropanation–ring expansion of 3-chloroindoles with α-halodiazoacetates: novel synthesis of 4-quinolone-3-carboxylic acid and norfloxacin - Peeters, Sara; Berntsen, Linn Neerbye; Rongved, Pål; Bonge-Hansen, Tore (Beilstein Journal of Organic Chemistry, 2019)
We present a short and efficient way of synthesizing two synthetically versatile 4-quinolone-3-carboxylate building blocks by cyclopropanation-ring expansion of 3-chloroindoles with α-halodiazoacetates as the key step. This novel transformation was applied towards the synthesis of the antibiotic drug norfloxacin.
Keywords: catalysis; cyclopropanation; indole; norfloxacin quinoline; quinolone; Rh(II); ring expansion

(untitled) - Davies, H. M. L.; Manning, J. R. (Nature, 2008)

Modern Catalytic Methods for Organic Synthesis with Diazo Compounds: From Cyclopropanes to Ylides - Doyle, M. P.; Mckervey, M. A.; Ye, T. (Wiley, 1998)

(untitled) - Davies, H. M. L.; Spangler, J. E. (Adv. Heterocycl. Chem., 2013)

(untitled) - Davies, H. M. L. (Adv. Nitrogen Heterocycl., 1995)

(untitled) - Davies, H. M. L.; Hedley, S. J. (Chem. Soc. Rev., 2007)

(untitled) - Ferreira, V. F. (Curr. Org. Chem., 2007)

(untitled) - Johansen, M. B.; Kerr, M. A. (Org. Lett., 2010)

(untitled) - Gibe, R.; Kerr, M. A. (J. Org. Chem., 2002)

(untitled) - Tsyshchuk, I. E.; Vorobyeva, D. V.; Peregudov, A. S.; Osipov, S. N. (Eur. J. Org. Chem., 2014)

(untitled) - Goto, T.; Natori, Y.; Takeda, K.; Nambu, H.; Hashimoto, S. (Tetrahedron: Asymmetry, 2011)

(untitled) - Zhang, X.-J.; Liu, S.-P.; Yan, M. (Chin. J. Chem., 2008)

(untitled) - Cai, Y.; Zhu, S.-F.; Wang, G.-P.; Zhou, Q.-L. (Adv. Synth. Catal., 2011)

(untitled) - Chan, W.-W.; Yeung, S.-H.; Zhou, Z.; Chan, A. S. C.; Yu, W.-Y. (Org. Lett., 2010)

(untitled) - Lian, Y.; Davies, H. M. L. (Org. Lett., 2012)

(untitled) - Mortén, M.; Hennum, M.; Bonge-Hansen, T. (Beilstein J. Org. Chem., 2015)

(untitled) - Bisacchi, G. S. (J. Med. Chem., 2015)

(untitled) - Mitscher, L. A. (Chem. Rev., 2005)

(untitled) - Haddad, N.; Tan, J.; Farina, V. (J. Org. Chem., 2006)

(untitled) - Huse, H.; Whiteley, M. (Chem. Rev., 2011)

(untitled) - Jadulco, R. C.; Pond, C. D.; Van Wagoner, R. M.; Koch, M.; Gideon, O. G.; Matainaho, T. K.; Piskaut, P.; Barrows, L. R. (J. Nat. Prod., 2014)

(untitled) - Abe, H.; Kawada, M.; Inoue, H.; Ohba, S.-i.; Nomoto, A.; Watanabe, T.; Shibasaki, M. (Org. Lett., 2013)

(untitled) - Baraldi, P. G.; Saponaro, G.; Moorman, A. R.; Romagnoli, R.; Preti, D.; Baraldi, S.; Ruggiero, E.; Varani, K.; Targa, M.; Vincenzi, F.; Borea, P. A.; Aghazadeh Tabrizi, M. (J. Med. Chem., 2012)

(untitled) - Hiltensperger, G.; Jones, N. G.; Niedermeier, S.; Stich, A.; Kaiser, M.; Jung, J.; Puhl, S.; Damme, A.; Braunschweig, H.; Meinel, L.; Engstler, M.; Holzgrabe, U. (J. Med. Chem., 2012)

(untitled) - Ma, L.; Seager, M. A.; Wittmann, M.; Jacobson, M.; Bickel, D.; Burno, M.; Jones, K.; Graufelds, V. K.; Xu, G.; Pearson, M.; McCampbell, A.; Gaspar, R.; et al. (Proc. Natl. Acad. Sci. U. S. A., 2009)

(untitled) - Lucero, B. d.; Gomes, C. R. B.; Frugulhetti, I. C. d. P. P.; Faro, L. V.; Alvarenga, L.; de Souza, M. C. B. V.; de Souza, T. M. L.; Ferreira, V. F. (Bioorg. Med. Chem. Lett., 2006)

(untitled) - Advani, R. H.; Hurwitz, H. I.; Gordon, M. S.; Ebbinghaus, S. W.; Mendelson, D. S.; Wakelee, H. A.; Hoch, U.; Silverman, J. A.; Havrilla, N. A.; Berman, C. J.; Fox, J. A.; Allen, R. S.; et al. (Clin. Cancer Res., 2010)

(untitled) - Anquetin, G.; Rouquayrol, M.; Mahmoudi, N.; Santillana-Hayat, M.; Gozalbes, R.; Greiner, J.; Farhati, K.; Derouin, F.; Guedj, R.; Vierling, P. (Bioorg. Med. Chem. Lett., 2004)

(untitled) - Mugnaini, C.; Pasquini, S.; Corelli, F. (Curr. Med. Chem., 2009)

(untitled) - Grohe, K.; Heitzer, H. (Liebigs Ann. Chem., 1987)

(untitled) - Gould, R. G.; Jacobs, W. A. (J. Am. Chem. Soc., 1939)

(untitled) - Torii, S.; Okumoto, H.; Long, H. X. (Tetrahedron Lett., 1990)

(untitled) - Vasudevan, N.; Jachak, G. R.; Reddy, D. S. (Eur. J. Org. Chem., 2015)

(untitled) - Heindel, N. D.; Fine, S. A. (J. Org. Chem., 1970)

(untitled) - Aldred, K. J.; Kerns, R. J.; Osheroff, N. (Biochemistry, 2014)

(untitled) - Bonge, H. T.; Pintea, B.; Hansen, T. (Org. Biomol. Chem., 2008)

(untitled) - Venepally, V.; Prasad, R. B. N.; Poornachandra, Y.; Kumar, C. G.; Jala, R. C. R. (Bioorg. Med. Chem. Lett., 2016)

(untitled) - Leyva, S.; Hernández, H. (J. Fluorine Chem., 2010)

(untitled) - Koga, H.; Itoh, A.; Murayama, S.; Suzue, S.; Irikura, T. (J. Med. Chem., 1980)